Estimation of Ophidiomyces prevalence to evaluate snake fungal disease risk. Issue 1 (4th October 2017) - Hileman, Eric T.; Allender, Matthew C.; Bradke, Danielle R.; Faust, Lisa J.; Moore, Jennifer A.; Ravesi, Michael J.; Tetzlaff, Sasha J.
ABSTRACT: Pathogenic fungi have become a global concern to wildlife populations over the last 2 decades. However, the threat of snake fungal disease (SFD; caused by Ophidiomyces ophiodiicola ) to snake populations is still largely unknown. From 2014–2016, we monitored 3 disjunct populations of the federally threated eastern massasauga ( Sistrurus catenatus ) in Michigan, USA. We used clinical signs of SFD, quantitative TaqMan polymerase chain reaction (qPCR), repeated sampling of individuals and sites, and single‐season occupancy models to estimate site‐specific prevalence of Ophidiomyces . Point estimates of Ophidiomyces prevalence in 2016 were larger at the northernmost study site (0.17, 95% CI = 0.04–0.50), where 17 of 34 snakes were implanted with radio‐transmitters, and smaller at southern sites (0.03, 95% CI = 0.00–0.19). However, Ophidiomyces prevalence was not different between snakes with transmitters and snakes without transmitters. Swabbing snakes with 1 applicator resulted in a high probability of failure in detecting Ophidiomyces DNA for individuals with clinical signs of SFD and the probability was even higher for individuals without clinical signs of SFD. Repeated sampling of individuals reduced the probability of obtaining a false‐negative qPCR result by 72% for snakes with clinical signs and 12% for snakes without clinical signs when we swabbed individuals with 5 applicators. We recommend resampling individuals and sites as a sampling design for estimating fine‐scale, site‐specific Ophidiomyces prevalence and population‐level responses to SFD. If clinical signs are used as a surrogate for SFD, we recommend researchers standardize diagnosis of clinical signs of SFD by providing technicians adequate field training and educational materials, and minimize the number of observers recording clinical signs. We discourage the use of radio‐telemetry methods where SFD occurs unless sterile surgical, handling, and equipment protocols can be ensured and the benefits to the population from such activities outweigh the increased health risks to individuals. © 2017 The Wildlife Society. Abstract : Accounting for imperfect detection, we demonstrated that prevalence of Ophidiomyces (the causative agent of snake fungal disease) varies across eastern massasauga populations in Michigan, USA, with higher prevalence at the northernmost study site (0.17, 95% CI = 0.04–0.50) and lower prevalence at the 2 southern localities (0.03, 95% CI = 0.00–0.19). Repeated sampling of individuals reduced the probability of failing to detect Ophidiomyces DNA when actually present (i.e., false negatives) by 72% for snakes with clinical signs and 12% for snakes without clinical signs when individuals were swabbed with 5 applicators.